FINANCIAL LITERACY TECHNOLOGY ADOPTION IN INDONESIAN SHARIA BANKING: A PRELIMINARY ANALYSIS - Silitonga, Riana Magdalena; Jou, Yung-Tsan; Sukwadi, Ronald; Pratama, Ferdian Aditya (Graduate Program of Universitas Tarumanagara, 2023)
The growth of financial instruments is significant nowadays. Because of that, more people are becoming more responsible in their financial planning, investment, and living expenses. Individuals who have financial knowledge tend to have more assets in finance in general. This research will study the readiness of technology adoption as its preliminary analysis for middle-lower socio-economics users in financial literacy of a leading Indonesian Sharia financial inclusion bank that focuses on women empowerment. In addition, this research also identifies the must-have features of the e-learning application. This research will conduct an online survey with 118 samples in Indonesia. This study found that West Java, South Borneo, and Southeast Sulawesi users are the most well-prepared to use technology to support their business. Some features like a group of learning materials and video-based learning are the most attractive features users desire to be accessible in the e-learning application.